Rekayasa Alat Pendeteksi Kebocoran Gas Berbasis Arduino Uno Dengan Sensor MQ-2 Pada Regulator LPG - ., Rahmatullah; Umurani, Khairul; Amiruddin, Arfis; Kurniawan, Wahyu; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2025)
The engineering of an Arduino Uno-based gas leak detection device with an MQ-2 sensor was created to optimize security against gas leaks that occur. The public must know the signs of a leak, such as smelling gas, a hissing sound in the gas line and so on. The aim of engineering this tool is to create an Arduino Uno-based gas leak detection tool that uses the MQ-2 sensor on the LPG regulator. Gas leaks can cause risks such as fire and explosion, so it is important to have a gas detection system. When the sensor detects the presence of gas, the system will trigger a buzzer to provide an audible alarm and turn on the LED light as a visual indicator. The LCD will display the detection status with clear text, namely